Digital Empowerment and E-Commerce Adoption among Handicraft SMEs: A Contemporary Islamic Economic Law Study Using the TOE Framework - Nuril Aulia Munawaroh; Sudarmiatin; Erry Tri Djatmika; Agus Hermawan; Miftahul Munir (Faculty of Sharia, IAIN Metro, 2025)
This study critically examines the integration of the Technology-Organisation-Environment (TOE) framework into digital empowerment practices among handicraft small and medium-sized enterprises (SMEs) from the perspective of contemporary Islamic economic law. The research aims to explore how technological readiness, organisational capacity, and environmental support influence the adoption of e-commerce, while aligning these dynamics with Islamic ethical and legal principles such as fairness (‘adl), transparency (shafāfiyyah), and social welfare (maṣlaḥah). Using a qualitative descriptive approach, this study synthesises empirical findings from relevant literature and case studies of handicraft SMEs that have implemented digital transformation strategies. The analysis reveals that the successful adoption of e-commerce within Islamic legal frameworks depends not only on technological and managerial factors but also on compliance with sharia-based economic values that promote justice, trust, and ethical business practices. The study concludes that integrating the TOE framework into digital empowerment provides a holistic model for sustainable SME development, bridging modern economic innovation with the moral foundations of Islamic law. The academic contribution of this study lies in its interdisciplinary integration of the TOE framework with contemporary Islamic economic jurisprudence, offering a novel analytical model that bridges digital innovation and normative Islamic law. It enriches the discourse on digital transformation in Muslim-majority economies by offering a sharia-compliant perspective on sustainable SME development and policy formulation.